2020
DOI: 10.1088/1757-899x/946/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Application of ternary logic for digital signal processing

Abstract: The article shown that digital processing of slowly changing signals based on ternary logic has significant advantages compared to processing based on binary logic. It is shown that for slowly changing signals, digital processing can be performed on the basis of dividing analysed signal into frequency bands. In particular, information on derivatives of a slowly varying signal which spectrum lies in the frequency band from 0 to ω_0, can be restored basing on the analysis of its component lying in the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The dependence of the relative illumination on the on-time recording photoresistor is shown in Figure 8. Examples of the data generated during measurement using the developed design are shown in Figures 8(a At this point, the tests of the device itself can be considered completed, since further data processing is already a task from the field of physical chemistry, which, however, does not exclude the possibility of using a variety of methods of digital signal processing, including those built on the basis of multivalued logic [29], [30]. This is especially true for such objects of research as liquids, in which HIA are formed.…”
Section: Test Results and Prospects For Further Development Of The Pr...mentioning
confidence: 99%
“…The dependence of the relative illumination on the on-time recording photoresistor is shown in Figure 8. Examples of the data generated during measurement using the developed design are shown in Figures 8(a At this point, the tests of the device itself can be considered completed, since further data processing is already a task from the field of physical chemistry, which, however, does not exclude the possibility of using a variety of methods of digital signal processing, including those built on the basis of multivalued logic [29], [30]. This is especially true for such objects of research as liquids, in which HIA are formed.…”
Section: Test Results and Prospects For Further Development Of The Pr...mentioning
confidence: 99%
“…There is also the possibility to implement operations in Galois fields using the usual "binary" element base. There are also some other possibilities, for example, related to the features of slowly changing signals, the "digital" derivatives of which can be found using frequency filtering [23] and using the apparatus of ternary logic [24], [25].…”
Section: Possibilities For Further Improvement Of the Proposed Methodsmentioning
confidence: 99%
“…Specifically, in the cited work, it is shown that the spectral range, in which concentrated the spectrum of a signal which is possessed of -coverage, is naturally divided into three sub-bands, two of which carry information about signal variations with an amplitude reduced to unity. This representation of signals turns out to be closely related to ternary logic [22], which serves as one more argument in favor of its use. This question can be posed even more broadly.…”
Section: Introductionmentioning
confidence: 91%
“…However, the possibilities of using multivalued logics have one more aspect, which has not yet received sufficient attention in the literature. Namely, multi-valued, in particular, ternary logic is a promising means of slowly changing signals [22] analyzing (more broadly, signals with a limited derivative). This line of research seems to be quite important, firstly, because many signals, for example, registered by monitoring systems [23], [24], really change rather slowly to the point that they described by functions with -coverage (the difference between signals at the next and previous unit of time by the module does not exceed one).…”
Section: Introductionmentioning
confidence: 99%